2008
DOI: 10.4219/jaa-2008-809
|View full text |Cite
|
Sign up to set email alerts
|

Quality of Instruction: Examining Discourse in Middle Schoo Mathematics Instruction

Abstract: According to the NCTM reform suggestions, when teachers are orchestrators of student interactions, students adopt a more active role in explaining and learning mathematics. This research, which mapped the nature and role of meaningful mathematical discourse, provides insights into discursive practices that lead to rich mathematical interactions. We observed, coded, and analyzed middle school algebra, number, and data lessons using a grounded theory approach. We organized the observed paths that emerged into a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
30
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 41 publications
(32 citation statements)
references
References 39 publications
(51 reference statements)
1
30
0
1
Order By: Relevance
“…Therefore, in order to deeply understand complex concepts, some form of discussion must take place-even if that conversation occurs within one individual. When considered in the classroom context, rich meaningful communication consists of "interactive and sustained discourses of a dialogic nature between teachers and students aligned to the content of the lesson that addresses specific student issues" [11] (p. 378). In other words, meaningful classroom discourse contributes to students' understanding by promoting effective communication and articulation of thought.…”
Section: Classroom Discoursementioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, in order to deeply understand complex concepts, some form of discussion must take place-even if that conversation occurs within one individual. When considered in the classroom context, rich meaningful communication consists of "interactive and sustained discourses of a dialogic nature between teachers and students aligned to the content of the lesson that addresses specific student issues" [11] (p. 378). In other words, meaningful classroom discourse contributes to students' understanding by promoting effective communication and articulation of thought.…”
Section: Classroom Discoursementioning
confidence: 99%
“…Through these interactions, students analyze and evaluate the mathematical thinking and strategies of others and deepen their own mathematical understanding. Students must organize and consolidate their mathematical thinking in order to communicate effectively with their classmates and with the teacher [7,11,[30][31][32]. Teachers' discourse practices also influence the nature of classroom discussions.…”
Section: Classroom Discoursementioning
confidence: 99%
See 1 more Smart Citation
“…Just as vocabulary development is essential for developing early reading skills, mathematics vocabulary development is key to build a foundation for later mathematics conceptual understanding [5,[10][11][12][13] (Samuels & Flor, 1997). These two vocabularies are interwoven in that the earlier a child can be exposed to mathematical vocabulary words representing concepts, the earlier that child could become proficient in the language of mathematics before formal instruction [4,14,15].…”
Section: Child Development Researchmentioning
confidence: 99%
“…Meanwhile, recent research from both educational and psychological perspectives has suggested that developmental milestones in reading and mathematics can be symbiotic [3,4]. One possible explanation for this connectivity is that students' understanding of mathematics concepts is bound to their mastering of content vocabularies that are used to define, represent, and communicate mathematical concepts [5]. It is feasible that improving children's application of mathematics vocabulary would yield a positive effect on their mathematics achievement.…”
Section: Introductionmentioning
confidence: 99%